Factors inducing career choice: Comparative study of five leading professions in Pakistan - Muhammad Nauman Abbasi; Nosheen Sarwat (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
This study aimed to identify major factors which induce Pakistani graduates while making their career choice. The current research investigated whether career choice factors vary across gender and among leading professions like management, agriculture, engineering, medical and pharmacy. Grounded from literature, a specially designed survey instrument was prepared and pilot tested for data collection. The final questionnaire pertained 24 items and was administered across a valuable sample of 370 students representing various disciplines from 8 different universities. Using principal component analysis, the items were grouped into five factors and were labeled as growth opportunities, occupational charm, self-esteem, societal inspiration and work related factors. The results significantly varied especially for medical, management and pharmacy professions and differed from previous investigations, illuminating the contextual importance of career choice factors. In terms of gender, females seemed more socially inspired as compared to their male counterparts while making a career choice.
Keywords: 330; career choice; higher education; leading professions; Pakistan